University Students Attitudes Towards Immigration Abroad in Light of Some Variables A Field Study on a Sample of Tishreen University Students - جديد لبنى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research aimed to identify the attitudes towards immigration abroad among Tishreen university students, as well as to detect differences in attitudes towards immigration abroad according to the variables gender and academic specialization, the research was conducted on a sample of Tishreen university students in the last academic year, there were 446 students, male and female In different Faculties ( Education and Psychology, Law, physical education, Arabic and English language, medicine, Nursing, Economics, Information Engineering and civil engineering). in the research the attitudes towards immigration Abroad questionnaire was used, prepared by the researcher after verifying its validity and reliability in the local environment. The research ended up: - Revealing the existence of an positive average level of attitudes towards immigration abroad. - There is no differences in attitudes towards immigration abroad according to gender. - There is no differences in attitudes towards immigration abroad according to the academic specialization (theoretical and applied faculties).